Coexistence of Urbach‐Tail‐Like Localized States and Metallic Conduction Channels in Nitrogen‐Doped 3D Curved Graphene. Issue 51 (18th November 2022) - Tanabe, Yoichi; Ito, Yoshikazu; Sugawara, Katsuaki; Jeong, Samuel; Ohto, Tatsuhiko; Nishiuchi, Tomohiko; Kawada, Naoaki; Kimura, Shojiro; Aleman, Christopher Florencio; Takahashi, Takashi; Kotani, Motoko; Chen, Mingwei
Abstract: Nitrogen (N) doping is one of the most effective approaches to tailor the chemical and physical properties of graphene. By the interplay between N dopants and 3D curvature of graphene lattices, N‐doped 3D graphene displays superior performance in electrocatalysis and solar‐energy harvesting for energy and environmental applications. However, the electrical transport properties and the electronic states, which are the key factors to understand the origins of the N‐doping effect in 3D graphene, are still missing. The electronic properties of N‐doped 3D graphene are systematically investigated by an electric‐double‐layer transistor method. It is demonstrated that Urbach‐tail‐like localized states are located around the neutral point of N‐doped 3D graphene with the background metallic transport channels. The dual nature of electronic states, generated by the synergistic effect of N dopants and 3D curvature of graphene, can be the electronic origin of the high electrocatalysis, enhanced molecular adsorption, and light absorption of N‐doped 3D graphene. Abstract : Nitrogen doping on 3D curved graphene leads to the coexistence of an Urbach‐tail‐like localized state and a metallic state. The dual nature of the electronic states can be the electronic origin of the high electrocatalysis, enhanced molecular adsorption, and light absorption of N‐doped 3D graphene.